Rhodium-Catalyzed Desymmetrization of meso-Glutaric Anhydrides to Access Enantioenriched anti,anti-Polypropionates - Cochran, Brian M.; Henderson, Daniel D.; Thullen, Scott M.; Rovis, Tomislav (Synlett, 2018)
An expedient desymmetrization of 3,5-dimethyl-4-alkoxyglutaric anhydrides to access anti,anti-polypropionates is described. The previously unknown anhydrides are rapidly assembled from readily available precursors. A Rh(I)·t-BuPHOX catalyst system was found to provide good yield and high selectivities. With these conditions, the trisubstituted anhydrides were desymmetrized with various alkyl zinc reagents to provide synthetically useful enantioenriched anti,anti-2,4-dimethyl-3-hydroxy-δ-ketoacids. An identical catalyst system also affords access to syn,syn-stereotriads as well as a partial kinetic resolution of a chiral anhydride.
Keywords: anhydride; desymmetrization; polypropionate; rhodium; zinc